DEVELOPING ENGLISH TEXTBOOK FOR MUHAMMADIYAH SCHOOL; AN IDEA TO INTEGRATE THE MUHAMMADIYAH VALUES INTO ELT - Septian Dwi Cahyo; Ika Rizqi Vitasari; Sucipto Sucipto (Universitas Ahmad Dahlan)
As the most common teaching materials, textbook always has significant impact toward English language teaching. An English textbook contains language culture, ideology, and behavior. While a common textbook is developed by mimicking the native language, it can be said that an English textbooks have secular knowledge for not integrating faith into its content. The Muhammadiyah proposed an education of coherence between knowledge and faith for better education by developing unique curriculum known as ISMUBA which is contain Islamic values and enhancing knowledge. The problem is most of teachers in the Muhammadiyah school use general English which does not meet with the Muhammadiyah education goal.This paper propose and give example of an idea to develop an English textbook for the Muhammadiyah schools by integrating the Muhammadiyah values into textbook. The textbook is developed by integrating Islamic values as base of language teaching materials. The textbook is also developed based on Kurikulum 2013 for English language teaching, so there is no contradiction of national education goal and the textbook itself. The textbook is developed in order to achieve coherence of knowledge and faith in the Muhammadiyah education